Change of Renal Parenchymal Width in Patients with Unilateral Ureteral Stent: A Bicenter Retrospective Study. (1st June 2017) - Kim, Hee Youn; Lee, Seung-Ju; Choi, Jin Bong; Yoo, Je Mo; Lee, Joon Ho; Lee, Dong Sup
Abstract : Purpose . To determine whether kidney sizes were changed after ureteral stents were instilled, and if so, what parameters were significant. Methods . Parenchymal width (PW) of 98 patients with unilateral ureteral stents was measured from the coronal view of CT scans for both stented and unstented contralateral kidney. The mean PW and % change of mean PW were calculated before stenting and at the time of last stent change. Estimated glomerular filtrate rate (eGFR) was recorded as well. Results . The mean duration of ureteral stent indwelled was 15.6 ± 10.2 (mean ± SD) months. The change of mean PW of stented kidneys and unstented contralateral kidneys was −16.9 ± 16.4 (mean ± SD)% and 3.6 ± 10.7 %, respectively. eGFR before and at the time of the last stent change did not show significant difference (p = 0.294 ). Duration of ureteral stent indwelled was found to be inversely related to the % change of mean PW (Spearman's correlation coefficient = −0.291, p < 0.001 ). Conclusions . For unilateral ureteral obstruction, kidney size was decreased over time in spite of indwelling ureteral stent. This finding can be overlooked by clinicians due to compensatory growth of contralateral kidney and resultant normal eGFR.